Characterization and process optimization of Collocalia Fuciphaga extract - Noor Suzana, Bakar (2012)
The purpose of this study is to characterize and investigate the optimum condition of temperature and liquid solid ratio (LSR)in Collocalia fuciphaga extract. The formation of functional group in the Collocalia fuciphaga was confirmed by fourier transform infrared spectroscopy(FTIR)analysis of the untreated and treated sample while inductively coupled plasma mass spectrometry (ICP-MS) was used to determine the heavy metals contents inside the Collocalia fuciphaga.Water extraction method was employed as a function of temperature and LSR in order to identify their effects to the protein extract concentration from Collocalia fuciphaga and subsequently determine its optimum condition using response surface methodology (RSM).The FTIR spectrums of the untreated and treated sample resulted in the same trend of spectrum. This is because the functional group of the protein extract, O-H bond,N-H bond, C=O bond,and C-H bond, respectively did not change after the extraction process. From the analysis using the ICP-MS, it was clearly showed that concentration of aluminium,arsenic and lead in the Collocalia fuciphaga was 2.378 mg/L, 0.044mg/L and 0.125mg/L which is lower than the maximum concentration allowable of aluminium, arsenic and lead (7mg/L,2mg/L and 3.402mg/L, respectively).The optimum condition of temperature and LSR were found to be 38OC and 42:1 while the protein extract concentration was 0.3477g/L.Increase in temperature after this optimum value resulted in decrease in protein extract concentration due to the destruction of protein structure at high temperature.